2018
DOI: 10.1038/s41598-018-23216-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of highly effective target genes for RNAi-mediated control of emerald ash borer, Agrilus planipennis

Abstract: Recent study has shown that RNA interference (RNAi) is efficient in emerald ash borer (EAB), Agrilus planipennis, and that ingestion of double-stranded RNA (dsRNA) targeting specific genes causes gene silencing and mortality in neonates. Here, we report on the identification of highly effective target genes for RNAi-mediated control of EAB. We screened 13 candidate genes in neonate larvae and selected the most effective target genes for further investigation, including their effect on EAB adults and on a non-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 26 publications
3
47
0
Order By: Relevance
“…In Agrilus planipennis larvae and adults, oral treatment of high concentrations of dsRNA (10 μg μL −1 ) targeting two vital genes, heat shock protein‐70 and shibire , showed ∼90% mortality. However, co‐treatment of both dsRNA at lower concentrations (1 μg μL −1 ) showed a synergistic effect with similar mortality rates (∼90%) . Similar effects were observed in T. castaneum fed with both Bip and Armet dsRNAs complexed with the BAPCs nanoparticle.…”
Section: Strategies For Oral Administration Of Dsrna In Insects and Isupporting
confidence: 61%
See 1 more Smart Citation
“…In Agrilus planipennis larvae and adults, oral treatment of high concentrations of dsRNA (10 μg μL −1 ) targeting two vital genes, heat shock protein‐70 and shibire , showed ∼90% mortality. However, co‐treatment of both dsRNA at lower concentrations (1 μg μL −1 ) showed a synergistic effect with similar mortality rates (∼90%) . Similar effects were observed in T. castaneum fed with both Bip and Armet dsRNAs complexed with the BAPCs nanoparticle.…”
Section: Strategies For Oral Administration Of Dsrna In Insects and Isupporting
confidence: 61%
“…However, co-treatment of both dsRNA at lower concentrations (1 μg μL −1 ) showed a synergistic effect with similar mortality rates (∼90%). 114 Similar effects were observed in T. castaneum fed with both Bip and Armet dsRNAs complexed with the BAPCs nanoparticle. The individual treatment of both dsR-NAs complexed with nanoparticles showed 25% mortality, but combined treatment resulted in 60% mortality.…”
Section: Combination or Stacked Treatmentssupporting
confidence: 56%
“…Interestingly, it was demonstrated that oral treatment of a combination of dsSHI and dsHSP70 at lower concentration by neonates and adults of Agrilus planipennis efficiently elicited mortality. Exposing adults to 1 µg/µL of dsSHI plus dsHSP70 caused 90% mortality after two weeks, whereas, 10 µg/µL of single dsRNA treatment exhibited lower mortality (up to 40%) [34]. Therefore, it may be worthwhile to test whether there is a combined effect by silencing both SHI and HSP70 in P. versicolora.…”
Section: Discussionmentioning
confidence: 99%
“…Newly hatched neonates were used in all bioassays. To determine the biological activity of the recombinant bacteria expressing dsRNA, neonate EAB larvae were fed using a modified droplet feeding bioassay [ 5 ], where 1 ml of bacterial culture was centrifuged at 3000 rpm for 15 min and the pellet was dissolved in 100 μL of 1% sucrose solution with green tracking dye (Kroger, Co., USA). For each assay, 3μL of bacterial suspension were fed to individual neonate larvae using the droplet assay.…”
Section: Methodsmentioning
confidence: 99%
“…Coleopteran insects are known to exhibit robust RNAi responses [ 2 , 4 , 5 ]. RNAi efficiency varies between insect species, insect life stages, target genes, and modes of dsRNA delivery [ 6 ]; dsRNA can be delivered in several ways, including by injection, orally, and through absorption [ 7 ].…”
Section: Introductionmentioning
confidence: 99%